1990
DOI: 10.1128/jvi.64.4.1437-1440.1990
|View full text |Cite
|
Sign up to set email alerts
|

Serum enhancement of human immunodeficiency virus (HIV) infection correlates with disease in HIV-infected individuals

Abstract: The sera from 16 individuals infected with the human immunodeficiency virus (HIV) at different clinical stages were evaluated for antibody-dependent neutralization and/or enhancement of infectivity by HIV. The HIV isolate from each individual (homotypic) and established laboratory strains showing broad cellular host range and cytopathicity were used. All sera could neutralize one of the laboratory-passaged isolates, whereas only two could neutralize the corresponding homotypic strain. Seven homotypic isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(52 citation statements)
references
References 22 publications
(35 reference statements)
0
52
0
Order By: Relevance
“…Importantly, ADE has also been described for HIV in vitro (26,27). Although it remains unknown whether ADE could increase HIV infection risk in humans (28), it has been found that patients with HIV who have antibodies capable of ADE have more rapid disease progression (29). For ADE to mediate enhanced infection risk after HIV vaccination, the vaccine regimen would need to induce nonneutralizing or poorly neutralizing antibodies; it has been shown that the HVTN 505 regimen did induce such antibodies (namely, gp41 reactive and nonneutralizing) (30).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, ADE has also been described for HIV in vitro (26,27). Although it remains unknown whether ADE could increase HIV infection risk in humans (28), it has been found that patients with HIV who have antibodies capable of ADE have more rapid disease progression (29). For ADE to mediate enhanced infection risk after HIV vaccination, the vaccine regimen would need to induce nonneutralizing or poorly neutralizing antibodies; it has been shown that the HVTN 505 regimen did induce such antibodies (namely, gp41 reactive and nonneutralizing) (30).…”
Section: Discussionmentioning
confidence: 99%
“…Except for early work with FcR-ADE [31], most data on the clinical significance were reported on C-ADE. Therefore, the following discussion will be largely restricted to the latter type of infection-enhancement.…”
Section: Antibody-dependent Enhancement Of Hiv Infectionmentioning
confidence: 99%
“…An attempt has been made to correlate the presence of enhancing Abs in the serum of HIV-infected patients to the progression of aquired immunodeficiency syndrome. However, the in vitro enhancement levels demonstrated were fairly low and the number of patients was limited (Homsy, et al, 1990). With HRSV, Ab may not only function to enhance infectivity, but also to enhance leukotriene production in infected cells (Ananaba and Anderson, 1991 ).…”
Section: Antibody-dependent Enhancement Of Virus Infectivitymentioning
confidence: 99%
“…The ultimate question is what bearing ADE of virus infection, as described in vitro, has upon the pathogenesis of disease in vivo and the development of virus vaccines. This question has fueled an ongoing debate among researchers ofDV (Halstead, 1989;Morens and Halstead, 1990;Rosen, 1989) and HIV (Bolognesi, 1989;Homsy, et al, 1990;Robinson, et al, 1988b). There is a substantial body of epidemiological information to suggest that ADE of DV infection of macrophages underlies the development of a more severe form of dengue called dengue hemorrhagic fever or dengue shock syndrome.…”
Section: Antibody-dependent Enhancement Of Virus Infectivitymentioning
confidence: 99%